The Effect of Marijuana Use on Personality Development in Adolescence and Young Adulthood. Issue 1 (1st January 2021) - McGehee, Rex
ABSTRACT: This paper considers the effects of marijuana on personality development during adolescence, integrating psychoanalytic views of development, information from neuroscience research, and recent social realities including legalization of marijuana in many states. The psychoanalytic treatment of a 16-year-old boy with marijuana dependence is presented. The paper concludes with recommendations for the treatment of adolescents who are marijuana users.